Analysis of Capital Adequacy in PT Bank Muamalat Indonesia Through Profitability, Financing Risk, and Cost Efficiency - Handika Adetama; Kusnendi Kusnendi; Aneu Cakhyaneu (Review of Islamic Economics and Finance, 2021)
AbstractPurpose - Capital is the main factor for a bank to be able to develop its business growth. The fulfillment of the Bank's Minimum Capital Ratio or known as CAR is determined by the BIS (Bank for International Settlement) at 8%. This study aims to determine and analyze the factors that affect the level of capital adequacy at Bank Muamalat Indonesia. The population in this study is all data on the financial statements of PT Bank Muamalat Indonesia for the period 20012-2019, which have been published on the official website of Bank Muamalat Indonesia, Bank Indonesia, and the Financial Services Authority. The sample in this study is quarterly financial report data on the CAR, ROA, NPF, and BOPO accounts in the financial statements of PT. Bank Muamalat Indonesia in the 2012-2019 period.Methodology - The method used in this research is the descriptive-explanatory method with multiple linear regression analysis. The dependent variable in this study is the Capital Adequacy Level. The independent variables in this study are Profitability Level (ROA), Financing Risk (NPF), and Cost Efficiency (BOPO).Findings - The study results show that the level of profitability and risk of financing has a significant effect on the level of capital adequacy at Bank Muamalat Indonesia. In contrast, the cost-efficiency variable has no significant effect. Partially shows the results that the level of profitability has a significant and significant effect on the level of capital adequacy in a positive direction, financing risk has a significant and significant effect on capital adequacy in a positive direction, and cost efficiency does not affect the amount of capital adequacy in a positive direction.Keywords - Capital Adequacy, Profitability, Financing Risk, Cost Efficiency